Effect of ozone on the reduction of bacterial load and on the maintenance of the physicochemical properties of milk: an alternative for human consumption - Soque , Alex (2019)
Background: Pasteurization of heavily contaminated milk, mainly with clostridial spores, is not safe because heat does not destroy this biological agent. An alternative is the use of ozone (O3), a highly oxidative gas with a broad antimicrobial spectrum, but the maximum dose that can be applied to food is unknown. Objective: To determine the dose and exposure time of raw milk to ozone, in order to reduce the bacterial load, without affecting the physical-chemical characteristics. Methods: Experimental study on raw milk samples grown before and after the application of ozone at different doses (50, 75 and 100 mg/L) and time periods (10, 20 and 30 minutes), total 9 groups (T1-T9) and a control group without O3 . The effect of ozone was evaluated through determination of the load of mesophiles, coliforms and Escherichia coli, as well as the physical chemical parameters in milk, compared to raw milk, boiled and ultrapasteurized milk Results: All treatments were effective in reducing the bacterial load with respect to raw milk. T9 (100 mg O3/L for 30 minutes) was the most effective, allowing a reduction of 64.87% (2.53 Log10 CFU/mL) of the initial total aerobic mesophil count, a 100% reduction (3.68 Log 10 CFU/mL) for total coliforms and a 100% reduction (3.67 Log10 CFU/ mL) for Escherichia coli. There were no physical-chemical changes in ozonized milk (P ≥0.05), but in boiled milk and UHT compared to raw milk. Conclusion: Ozonation is effective in reducing the bacterial load of raw milk, without altering its physical-chemical characteristics.